2017
DOI: 10.1186/s12879-017-2555-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of acute hepatitis A outbreak in Taiwan, 2015–2016: observations from a tertiary medical center

Abstract: BackgroundAcute hepatitis A is a fecal-oral transmitted disease related to inadequate sanitary conditions. In addition to its traditional classification, several outbreaks in the men who have sex with men (MSM) population have resulted in acute hepatitis A being recognized as a sexually transmitted disease. However, few studies have clarified the clinical manifestations in these outbreaks involving the MSM population.MethodsBeginning in June 2015, there was an outbreak of acute hepatitis A involving the MSM po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Some publications suggest different clinical course and disease severity when hepatitis A occurs in MSM or HIV‐infected patients . The aim of this study was to analyse the demographics, risk factors, comorbidities and laboratory results of hospitalized cases of acute hepatitis A in two tertiary level hospitals in Northern Italy (Fondazione IRCCS Policlinico San Matteo Pavia and Milan Niguarda Hospital) in 2017 and in the 2009‐2016 period, to evaluate whether HIV infection or MSM status can affect the clinical course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some publications suggest different clinical course and disease severity when hepatitis A occurs in MSM or HIV‐infected patients . The aim of this study was to analyse the demographics, risk factors, comorbidities and laboratory results of hospitalized cases of acute hepatitis A in two tertiary level hospitals in Northern Italy (Fondazione IRCCS Policlinico San Matteo Pavia and Milan Niguarda Hospital) in 2017 and in the 2009‐2016 period, to evaluate whether HIV infection or MSM status can affect the clinical course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of acute hepatitis A among those at‐risk populations have been described since the 1980s and have reemerged across the Asia‐Pacific region, the United States, and several European countries since 2015 . In Taiwan, an unprecedented outbreak with more than 1,000 indigenous cases of acute hepatitis A occurred in 2015‐2016, which was characterized by a high proportion of MSM and human immunodeficiency virus (HIV)–positive individuals . Furthermore, phylogenetic analysis demonstrated that the outbreak strains in Taiwan and The Netherlands were identical, suggesting that HAV might have been transmitted through sexual networks and international travel …”
mentioning
confidence: 99%
“…In high‐income countries, the transmission route through sexual contacts is the one mainly linked to outbreaks, and thus MSM and HIV‐positive patients represent the most important target groups for vaccination campaigns. Although no death was registered in our centre, recent studies report fatal courses during this outbreak . Fulminant hepatitis A is, in fact, a deadly disease, with pre‐existing liver disease and a history of alcohol or drug abuse being risk factors for a fatal outcome.…”
Section: Discussionmentioning
confidence: 76%